Pengaruh Likuiditas, Solvabilitas, Profitabilitas Terhadap Opini Audit : Studi Empiris Pada Laporan Keuangan Tahun 2019-2023 Perusahaan Perbankan Yang Terdaftar Di BEI - Ester Talenta Novjalia Marbun; Febriani Putri Lestari; Kesia Datubara; , Magdalena; Meilinda Sapta Dika; Napa; Putri Lestari; Riska Yulandari; Syifa Aulia; Tiara Saputri; Brigita Berlian (Economic Reviews Journal, 2025)
Audit opinion is where the auditor analyzes financial ratios such as LDR, CR, CAR, DER, NIM, ROA and ROE to assess the financial health of a company. High CR and ROA reflect profitability and provide a positive signal to investors. On the other hand, a balanced LDR helps maintain liquidity. A high CAR reflects the financial stability of a company, while a high DER indicates high debt which can reduce investor interest. A good NIM will increase a company's profitability and contribute to increasing ROE. The aim of this research is to understand the impact of liquidity, solvency and profitability on audit opinions, as well as to provide the impact of LDR, CR, CAR, DER, NIM, ROA and ROE. The sample in this study used samples from eight state-owned banking companies listed on the Indonesia Stock Exchange between 2019 and 2023. The total sample was 20 people, the technique used was purposive sampling. In this research, the analysis uses the associative analysis method, namely advanced logistic regression. The results of this research show that CR, DER, ROA and company size have a significant influence on audit opinion, but revenue growth does not have a significant influence.